A Temporal Neural Trace of Wavelet Coefficients in Human Object Vision: An MEG Study - Hatamimajoumerd, Elaheh; Talebpour, Alireza (Frontiers in Neural Circuits, 2019)
Wavelet transform has been widely used in image and signal processing applications such as denoising and compression. In this study, we explore the relation of wavelet representation of stimuli with MEG signal acquired from a human object recognition experiment. To investigate the signature of wavelet descriptors in the visual system, we apply five level of multi-resolution wavelet decomposition to the stimuli presented to participants during MEG recording, and extract the approximation and details's (horizontal, vertical, diagonal) sub-bands coefficients in each level of decomposition. Besides, by employing multivariate pattern analysis (MVPA), a linear support vector classifier (SVM) is trained and tested over the time on MEG pattern vectors to decode neural information. Then, we calculate the representational dissimilarity matrix (RDM) in each time point of the MEG data and also one RDM for each wavelet descriptors using classifier accuracy and one minus Pearson correlation coefficient respectively. Given the time-courses calculated from performing the Spearman correlation between the wavelet descriptors’ RDMs and MEG decoding accuracy in each time point, our result shows that the peak latency of the wavelet approximation time courses occurs later for higher level coefficients. Furthermore, studying the neural trace of details sub-bands coefficients indicates that the overall number of statistically significant time points for horizontal and vertical detail coefficients is noticeably higher than diagonal detail coefficients, confirming the evidence of the oblique effect that the horizontal and vertical lines are more decodable in the human brain.